Autonomia, autoridade e formação moral em Kant e Piaget - Smaniotto, Daiana Michelle (2015)
This study is part of the Education Philosophy field, in order to discuss the adult role in the formation of the moral subject process in Kant and Piaget. The issue of research focuses on the question: what does it significate to educate for autonomy and morality in studies of Kant and of the Young Piaget? The question treatment presupposes the in vestigation on how Kant and Jean Piaget understood the exercise of authority in educational and social relationships. For this, is has been realized the research focusing the study on passages from the works On the pedagogy of Kant, Kant & education of Dalbosco, About the education and the moral judgment on the child of Jean Piaget. It is believed that a significant part of the thesis of Kant around children's moral formation remains current, consistent with experimental and empirical researches of genetic psychology carried out by the young Piaget. The central aspect of the text is in the development of autonomy and children’s moral education against tension between autonomy and heteronomy in the relationship between children and adults. For Kant and Piaget children's moral conscience is not innate, that is, it results from the rational development and social relations between people. However, Kant proposes the relationship between adults and children, while Piaget defends children's relationships with thei r peers of the same age, considering the existence of "spontaneous children's societies." For Piaget, these child relationships are developed in a very important way of reciprocity and cooperation, key aspects in the formation of morality and their own thought.